The Role of Sembung (Blumea balsamifera) Leaf Extract in Preventing Atherosclerosis in Hyperlipidemia Rat Models (Biosaintifika: Journal of Biology & Biology Education, 2024)
This study aims to prove that administering BBLE as a natural antioxidant can prevent atherosclerosis by maintaining lipid profiles, antioxidant enzymes, and netrin-1 levels in hyperlipidemia in rat models. The research subjects were 20 adult male Wistar rats (Rattus norvegicus), which were divided into 2 groups using a randomized pretest and posttest control group design. Before treatment and after treatment for 3 months, lipid profiles, MDA, SOD, and netrin-1  were examined. The control group was only given high-cholesterol diets (HCD), while the treatment, apart from HCD, was also given BBLE 4mg/day. The data obtained was tested using paired t-test and group t-test. The results of the study showed that there was a significant decrease in netrin-1 in the control group (p0.05). Netrin-1 levels in the treatment group were higher than the control (p